Computer simulation of a permeable generator thermoelement - Anatychuk , L.I.; Cherkez, R.G.; Shcherbatyi, D.V. (Journal of Thermoelectricity, 2021)
The paper presents the results of computer studies of a 3D model of a permeable generator thermoelement. A physical model and design of a permeable thermoelement are given, and its mathematical description is presented. A method for calculating a thermoelement based on the Comsol Multiphysics software package has been developed. The dependences of the energy characteristics of a thermoelement made of Bi-Te-Se-Sb based materials on the height of the thermoelement leg are calculated.